Impact Analysis of Pipe Jacking Crossing and Parallel Construction on Existing Metro Shield Tunnels - HUANG Jianhua; YUAN Xiaoyu; ZHANG Jiankun (Chengshi guidao jiaotong yanjiu)
［Objective］ In underground excavation projects, the working conditions of tunnels crossing each other are becoming increasingly frequent and complex. It is therefore imperative to investigate their interactions and mutual impact mechanisms to control tunnel deformation within a reasonable range. ［Method］ Based on an engineering case of pipe jacking crossing an existing shield tunnel, a simulation analysis is conducted to study the impact patterns of pipe jacking and parallel construction on the existing metro shield tunnel, and the results are validated against actual measurement data. ［Result & Conclusion］ The deformation of existing tunnel decreases as the distance from the pipe jacking expands. During the pipe jacking vertical crossing, the maximum deformation of the existing metro tunnel occurs at the central axis of the pipe jacking. Within 12 meters of the pipe jacking excavation face from the central axis of the metro shield tunnel, the deformation of the metro shield tunnel reaches its maximum. For pipe jacking parallel crossing construction, the influence zone primarily extends 20 meters ahead of and 10 meters behind the pipe jacking excavation face.